2021
DOI: 10.1007/s11356-021-15443-8
|View full text |Cite
|
Sign up to set email alerts
|

Spa therapy interventions for post respiratory rehabilitation in COVID-19 subjects: does the review of recent evidence suggest a role?

Abstract: Pulmonary rehabilitation is essential in post-COVID subjects, reporting respiratory impairment after the discharge from the hospital. Because the number of patients with respiratory outcomes is high and there are few facilities available, we wonder if a spa setting could represent a valid out-of-hospital alternative. We aim to explore recent evidence related to respiratory rehabilitation in the spa environment to understand if it can represent an appropriate setting for respiratory rehabilitation interventions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 29 publications
0
24
0
2
Order By: Relevance
“…Respiratory performance also appears to improve with the application of a water exercise program, reconfirming what has already been suggested in the literature. 19 Since patients with chronic fatigue and reduced exercise tolerance are increasing worldwide in proportion to the increase in COVID-19 infection cases, there is an urgent need for innovative and effective protocols to treat these subjects. In recent months, it has already been suggested that specific water exercise protocols, including the use of thermal water and the adoption of multidisciplinary interventions (motor programs, respiratory rehabilitation and neuropsychological interventions), can be employed to treat chronic fatigue in post COVID-19 subjects.…”
Section: Rehabilitation Program Including Aqua Exercises In Freshwate...mentioning
confidence: 99%
See 2 more Smart Citations
“…Respiratory performance also appears to improve with the application of a water exercise program, reconfirming what has already been suggested in the literature. 19 Since patients with chronic fatigue and reduced exercise tolerance are increasing worldwide in proportion to the increase in COVID-19 infection cases, there is an urgent need for innovative and effective protocols to treat these subjects. In recent months, it has already been suggested that specific water exercise protocols, including the use of thermal water and the adoption of multidisciplinary interventions (motor programs, respiratory rehabilitation and neuropsychological interventions), can be employed to treat chronic fatigue in post COVID-19 subjects.…”
Section: Rehabilitation Program Including Aqua Exercises In Freshwate...mentioning
confidence: 99%
“…In recent months, it has already been suggested that specific water exercise protocols, including the use of thermal water and the adoption of multidisciplinary interventions (motor programs, respiratory rehabilitation and neuropsychological interventions), can be employed to treat chronic fatigue in post COVID-19 subjects. 20 Thermal mineral water-based treatments may improve the physical symptoms of chronic fatigue and modulate the immune imbalance, reducing persisting inflammation. Additionally, rehabilitative protocol in the aquatic setting could also properly address comorbidities that can be present in post-COVID patients, such as obesity and other neurological and/or musculoskeletal problems.…”
Section: Rehabilitation Program Including Aqua Exercises In Freshwate...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the inexpensive nature of spa therapy would represent a relevant financial strategy in the medico-economic management of the present health crisis (Kardeş 2021 ). While the pandemic crisis and the consecutive lockdowns distancing restrictions have critically affected their activity, hydrothermal centers should then be considered today as medically and economically pertinent alternatives to face the urgent need for interventions among COVID-19 patients (Masiero et al 2020a , b ; Maccarone and Masiero 2021 ; Kardeş 2021 ). Indeed, beyond the virtues of thermal waters, thermal institutions present several multidisciplinary health care programs combining alternative medicine with respiratory care, adapted physical activity programs, nutritional support, psychological support, physiotherapy, massage, music, or aromatherapy, in relaxing environments and under medical supervision.…”
Section: What About Hydrotherapeutic Multidisciplinary Approaches ?mentioning
confidence: 99%
“…Yet, other types of alternative medicines have also been proposed as innovative rehabilitative treatments, such as health resort medicine that has been suggested as a suitable setting to take care of discharged patients (Masiero et al 2020a). Since much evidence demonstrated the efficiency of spa environment on several respiratory diseases, spa setting might indeed represent a relevant out-of-hospital alternative (Maccarone and Masiero 2021), especially in the context of an increasing number of patients with respiratory outcomes whereas only a few facilities remain available. As mineral-rich waters were found to improve immune function, the potential benefits of such waters might also be discussed in the era of COVID-19 (Masiero et al 2020b).…”
Section: What About Hydrotherapeutic Multidisciplinary Approaches ?mentioning
confidence: 99%